Impact Health Fitness on Weight Body of Middle-aged Women - Koziy, Tatyana; Tarasova, Olga; Karpuhina, Yulia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper is devoted to studies the dynamics of indicators of morphological parameters of middle-aged women when doing wellness fitness. It is shown that under the influence of exercise training programs, aqua aerobics and shaping anthropometric status of women is significantly improved, as evidenced by their significant reduction